Advances in spatial and temporal databases: 15th International Symposium, SSTD 2017 : Arlington, VA, USA, August 21-23, 2017 : proceedings - Gertz, Michael; Renz, Matthias; Zhou, Xiaofang; Hoel, Erik; Ku, Wei-Shinn; Voisard, Agnès; Zhang, Chengyang; Chen, Haiquan; Tang, Liang; Huang, Yan (Springer International Publishing AG, 2017)
Intro -- Preface -- Organization -- Contents -- Routing and Trajectories -- Multi-user Itinerary Planning for Optimal Group Preference -- 1 Introduction -- 2 Problem Definition and Preliminaries -- 3 Proposed Solutions -- 3.1 Meeting Graph and Node Profit -- 3.2 Greedy Itinerary Construction -- 3.3 Optimal Itinerary Construction -- 3.4 Acceleration via Graph Compression -- 4 Related Work -- 5 Experiments -- 5.1 Experiment Design -- 5.2 Experimental Results -- 6 Discussions and Conclusion -- References -- Hybrid Best-First Greedy Search for Orienteering with Category Constraints -- 1 Introduction -- 2 Related Work -- 3 Problem Formalization -- 4 Best-First Search Strategy -- 4.1 Potential Score -- 4.2 Our Algorithm -- 4.3 Further Optimizations -- 5 Approximation Algorithms -- 5.1 Bounding the Score -- 5.2 Bounding the Run Time -- 6 Properties and Bounds -- 6.1 Correctness of Pruning -- 6.2 Lower Bounding the Score -- 6.3 Upper Bounding the Run Time -- 7 Experimental Evaluation -- 7.1 Data Sets -- 7.2 Effects of Parameters -- 7.3 Comparison with Competitors -- 8 Conclusion and Future Work -- References -- On Privacy in Spatio-Temporal Data: User Identification Using Microblog Data -- 1 Introduction -- 2 Related Work -- 2.1 User Identification -- 2.2 User Linkage -- 2.3 Spatial Privacy -- 3 Problem Definition -- 4 Trajectory Based User Identification -- 4.1 Trace Profile Modeling -- 4.2 Set Descriptors -- 4.3 Transition Descriptors -- 4.4 Classification -- 4.5 User Linkage -- 5 Experimental Evaluation -- 5.1 Accuracy Using Set Descriptors -- 5.2 Accuracy Using Frequent Transitions -- 5.3 Accuracy for Different Observation Counts -- 5.4 User Linkage Between Different Social Networks -- 5.5 Scalability -- 6 Conclusions -- References -- Big Spatial Data -- Sphinx: Empowering Impala for Efficient Execution of SQL Queries on Big Spatial Data.
Description based on publisher supplied metadata and other sources
Keywords: Konferenzschrift; Data Mining; Räumliches Datenbanksystem; Zeitliches Datenbanksystem